Complex Regulation Pathways of AmpC-Mediated β-Lactam Resistance in Enterobacter cloacae Complex - Guérin, François (Antimicrob Agents Chemother, 2015)
Enterobacter cloacae complex (ECC), an opportunistic pathogen causing numerous infections in hospitalized patients worldwide, is able to resist β-lactams mainly by producing the AmpC β-lactamase enzyme. AmpC expression is highly inducible in the presence of some β-lactams, but the underlying genetic regulation, which is intricately linked to peptidoglycan recycling, is still poorly understood. In this study, we constructed different mutant strains that were affected in genes encoding enzymes suspected to be involved in this pathway. As expected, the inactivation of ampC, ampR (which encodes the regulator protein of ampC), and ampG (encoding a permease) abolished β-lactam resistance. Reverse transcription-quantitative PCR (qRT-PCR) experiments combined with phenotypic studies showed that cefotaxime (at high concentrations) and cefoxitin induced the expression of ampC in different ways: one involving NagZ (a N-acetyl-β-d-glucosaminidase) and another independent of NagZ. Unlike the model established for Pseudomonas aeruginosa, inactivation of DacB (also known as PBP4) was not responsible for a constitutive ampC overexpression in ECC, whereas it caused AmpC-mediated high-level β-lactam resistance, suggesting a post-transcriptional regulation mechanism. Global transcriptomic analysis by transcriptome sequencing (RNA-seq) of a dacB deletion mutant confirmed these results. Lastly, analysis of 37 ECC clinical isolates showed that amino acid changes in the AmpD sequence were likely the most crucial event involved in the development of high-level β-lactam resistance in vivo as opposed to P. aeruginosa where dacB mutations have been commonly found. These findings bring new elements for a better understanding of β-lactam resistance in ECC, which is essential for the identification of novel potential drug targets.